2024
DOI: 10.3390/nu16030433
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Oil Improves Emphysema in Cigarette Smoke Extract-Induced Mice through Anti-Inflammatory and Antioxidative Effects

Aikkarach Kettawan,
Sukpattaraporn Ruangklai,
Thanaporn Rungruang
et al.

Abstract: Lung inflammation and alveolar enlargement are the major pathological conditions of chronic obstructive pulmonary disease (COPD) patients. Rice bran oil (RBO), a natural anti-inflammatory and antioxidative agent, has been used for therapeutic purposes in several inflammatory diseases. This study aimed to investigate the anti-inflammatory and antioxidative effect of RBO on a cigarette smoke extract (CSE)-induced emphysema model in mice. The results indicated that CSE significantly induced airspace enlargement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The IP injection model can also be established without the requirement of a longer treatment time (usually 3-6 weeks) [38,39]. Recent studies comparing CS exposure with IP injection models demonstrated comparable preclinical outcomes when looking at key COPD features, including the extent of lung damages (emphysema) and lung inflammatory changes [19,[40][41][42]. Nonetheless, mice exposed to CSE represent one of the most commonly used models of COPD [34,35,39].…”
Section: Discussionmentioning
confidence: 99%
“…The IP injection model can also be established without the requirement of a longer treatment time (usually 3-6 weeks) [38,39]. Recent studies comparing CS exposure with IP injection models demonstrated comparable preclinical outcomes when looking at key COPD features, including the extent of lung damages (emphysema) and lung inflammatory changes [19,[40][41][42]. Nonetheless, mice exposed to CSE represent one of the most commonly used models of COPD [34,35,39].…”
Section: Discussionmentioning
confidence: 99%